Ensuring Integrity in Orthopaedic Research: Addressing Unethical Practices and Promoting Ethical Standards - Vaishya, Raju; Bhadani, Janki Sharan; Vaish, Abhishek; Joshi, Pramod (Journal of Nepal Health Research Council, 2025)
This review discusses the prevalence of these unethical behaviours, their far-reaching consequences on patient care, and the Orthopaedic field’s credibility. It highlights the need for effective strategies to promote ethical standards, emphasizing the importance of awareness among researchers and clinicians. The article outlines specific unethical practices, including data manipulation, which distorts treatment efficacy, and plagiarism, which diminishes originality and wastes peer review resources. Additionally, it addresses biased reporting and conflicts of interest, which can compromise objectivity in research findings. The review advocates for collaborative efforts among institutions and journals to foster accountability and transparency, ultimately encouraging a culture of ethical conduct within the Orthopaedic community. By ensuring rigorous standards and practices, the future of Orthopaedic research can be aligned with patient safety and trust, propelling the field toward meaningful advancements in patient care and treatment outcomes.Keywords: Conflict of interest; data fabrication; ethics; plagiarism; research; research Integrity.